Chlorogenic Acid Protects Against Indomethacin-Induced Inflammation and Mucosa Damage by Decreasing Bacteroides-Derived LPS - Yan, Yongwang; Zhou, Xu; Guo, Kangxiao; Zhou, Feng; Yang, Hongqi (Frontiers in Immunology, 2020)
Background: Chlorogenic acid (CGA), a natural bioactive polyphenol, exerts anti-inflammatory, antioxidant, and antibacterial effects that support the maintenance of intestinal health. However, the influence of CGA on gut microbiota and their metabolites, as well as its potential effects and mechanism of action in inflammatory bowel disease, remain to be elucidated. Methods: First, an oral gavage was used to administer CGA to indomethacin-treated mice. Then, fecal microbiota transplantation was performed to explore the role of intestinal microbiota in indomethacin-induced inflammation. Results: CGA treatment protected against body weight loss, damage to intestinal morphology and integrity, inflammation, and alteration of microbiota composition in indomethacin-treated mice. Interestingly, CGA failed to inhibit inflammation or protect intestine integrity in mice treated with antibiotics. Notably, mice who had been colonized with intestinal microbiota from CGA-treated or CGA-and-indomethacin-treated mice, through the fecal microbiota transplantation program, were protected from indomethacin-induced inflammation, growth of Bacteroides, and the accumulation of Bacteroides-derived LPS, in congruence with those who had been treated with CGA. Conclusion: The results suggest that CGA may protect intestine integrity and alleviate inflammatory responses, primarily by inhibiting the growth of Bacteroides and the accumulation of Bacteroides-derived LPS, in indomethacin-induced colitis. This newly identified mechanism broadens our knowledge of how CGA exerts protective effects on intestinal inflammation and provides strategies for the prevention of gastrointestinal mucosal damage in patients treated with indomethacin.